Changing the routine: a move to patient initiated follow up to improve surgical outpatient clinic. Issue 6 (16th April 2022) - Balhorn, Joshua; Su'a, Bruce; Jin, James; Peng, Sze‐Lin; Weston, Maree; Israel, Lincoln; Connolly, Andrew; Hill, Andrew G.; Taneja, Ashish
Abstract: Introduction: Patient initiated follow up (PIFU) allows patients to initiate a hospital follow up appointment on an 'as required' basis in contrast to the traditional physician‐initiated model. We present a clinical pathway for patients referred with rectal bleeding at a large tertiary public hospital in South Auckland, New Zealand and demonstrate the utility of PIFU and its impact on reducing follow up appointments. Method: The purpose of the pathway was to allow standardized care by the clinicians and allow for PIFU. Two separate protocols were developed ‐ 'Painful PR bleeding' and 'Painless PR bleeding'. A new clinic (NC) was started following these protocols, and this was compared to historical controls (HC). The primary outcome was the rate of follow up appointments. Results: There were 133 patients in the NC and 135 in the HC, with significantly less follow ups in the NC (6% versus 45%, p < 0.0001). A small percentage of patients in the NC group were directly discharged (10%) whilst 70% of patients were discharged with a PIFU card. Thirty phone calls were made using PIFU, with 10 patients returning to clinic and 20 requiring advice and reassurance only. At 5 year follow up, there was a single colorectal malignancy found in both groups. Conclusion: Initiating a protocol that includes patient initiated follow up vastly reduces the need for routine return to clinic for the majority of patients, without sacrificing patient care. A protocolised approach to clinic for other areas in general surgery should be considered. Abstract : Historically patients have often been followed up routinely for benign anorectal conditions, which places a large strain on outpatient clinic resources. Patient initiated follow up instead puts the onus on the patient to arrange further appointments if they need further input. Protocolising clinic visits allows for guidelines to follow so that every patient gets equal and quality care.